The biogeophysical impacts of land cover change on climate extremes in the Arctic and Boreal regions - Shuai Li; Di Yang; Yaqian He; Nicholas Parazoo; Wei Liu (Environmental Research Letters, 2025)
Land cover change (LCC)-climate interactions could amplify or mitigate climate change in the Arctic and Boreal regions. Revealing the impacts of LCC on climate extremes helps to improve risk assessment capability and provides targeted adaptation and mitigation strategies to enhance regional climate resilience. In this study, we parameterized remotely-sensed land cover maps into the Community Earth System Model version 2 (CESM2) to examine the biogeophysical effects of LCC on temperature and precipitation extremes in the Arctic–Boreal Vulnerability Experiment (ABoVE) core domain, where the contribution of substantial LCC to abnormal climate variations has been little explored. Results showed that LCC had varying degrees of impact on regional climate extremes. Alteration in surface albedo induced net radiation changes, which further resulted in variation in maximum temperature (Tmax), with ice days (ID) and warm spell duration index (WSDI) increased by more than 3 days, and the maximum value of daily maximum temperature (TXx) decreased by more than 0.6 °C. The LCC-induced combined effects of water vapor supply and atmospheric dynamics resulted in a decreasing trend in precipitation extreme, with the number of days with precipitation exceeding 10 mm (R10mm) and annual total precipitation in days with precipitation exceeding 1 mm (PRCPTOT) decreased by more than 3 days and 15 mm, respectively, while consecutive dry days (CDD) increased by more than 3 days. These findings highlight the importance of LCC for regional climate variability in the Arctic and Boreal regions, contribute to a better understanding of LCC-climate interactions.